THU0451 Sensitivity to Change of SF-36 Health Survey and Patient Generated Index in People with Chronic Knee Pain Commenced on Oral Analgesia: Analysis of Data from a Clinical Trial. (9th June 2015) - Papou, A.; Hussain, S.; McWilliams, D.; Zhang, W.; Doherty, M.
Abstract : Background: Over the last few decades, health-related quality of life (HRQoL) instruments have been developed for the assessment of the efficacy of various treatments and healthcare delivery decisions, especially in chronic painful conditions such as osteoarthritis (OA). There are constant debates about which HRQoL tool is most sensitive and captures all appropriate information. This study was developed to compare the efficacy of two different tools; the person-specific "Patient Generated Index" (PGI) and the generic "Short Form 36 Health Survey" (SF-36), where to date only few studies have compared them in people with rheumatic conditions. Objectives: To compare sensitivity to change (STC) of the SF-36 and PGI in patients with knee pain commenced on oral analgesics, and to identify factors that influence the results. Methods: An observational study nested within a randomised controlled trial comparing oral paracetamol, oral ibuprofen or the combination of both in 884 community-derived participants aged 40 years and older with chronic knee pain (1). Each participant was given the SF-36 and PGI questionnaires to fill out at baseline, day 10, week 7 and week 13 after commencement on analgesia. The STC was calculated for 8 domains and 2 summary scores of the SF-36 and for the PGI. A qualitative analysis was undertaken to identify prevailing domains in the PGI, their frequency, and areas of life which are of most concern to the participants. Results: 85% of the participants satisfied American College of Rheumatology criteria for knee OA (1986). The PGI showed the greatest sensitivity to change to analgesics by week 13 (STC 0.61, 95% confidence interval (CI) 0.51 to 0.72), and only the Bodily Pain Score of the SF-36 showed a similar size of STC (0.49, 95%CI 0.39 to 0.58). Other SF-36 domains and both summary scores - Physical Component Score (PCS) and Mental Component Score (MCS) were all less responsive than the PGI, although the PCS had STC similar to the PGI with shorter term analgesia (figure 1 ). Qualitative analysis of the PGI identified multiple, highly individualised areas which are not represented in the SF-36 which may help explain its performance (such as many individual sports activities, gardening, family and relationships, driving, hobbies, etc). Conclusions: Overall the PGI is more sensitive than the SF-36 to improvements obtained from over-the-counter oral analgesics (paracetamol and/or ibuprofen) taken for knee pain in OA. The PGI is able to elicit areas of individualised HRQoL which are not captured by the SF-36. References: Doherty M, Hawkey C, Goulder M, Gibb I, Hill N, Aspley S, et al. A randomised controlled trial of ibuprofen, paracetamol or a combination tablet of ibuprofen/paracetamol in community-derived people with knee pain. Annals of the rheumatic diseases. 2011;70(9):1534-41. Acknowledgements: The authors are grateful to Reckitt Benckiser Healthcare International Ltd for financial support for the initial RCT and to the other investigators and research nurses involved in the RCT which generated the data analysed in the present study. Disclosure of Interest: None declared